Entrepreneurship Integration in The Islamic Higher Education Curriculum and Its Benefits for Muslim Communities - Inayatul Ulya (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2018)
Entrepreneurship integration in the Islamic higher education curriculum is a concept of curriculum development that is designed in harmony with the aspirations and needs that arise in society. Thus, the conceptual reference to curriculum development is expected to produce graduates who have competencies in the academic and entrepreneurial fields, have an entrepreneurial spirit by implementing entrepreneurial values and giving hope for alternative jobs outside their academic path. So that Islamic higher education graduates can compete in the job market, have quality and expertise, work ethics, creative and innovative ideas in their lives. This study used a qualitative research with a primary focus on curriculum studies in Islamic Higher Education through the identification of problems and needs based curriculum development of entrepreneurship. The final result of this research is the design of entrepreneurship integration in the Islamic Higher Education curriculum. The benefits of entrepreneurship education in the development of Muslim communities can be a spirit of expanding employment, encouraging economic power, the emergence of Muslim entrepreneurs and fostering a work ethic for Muslim communities.